High Levels of Eomes Promote Exhaustion of Anti-tumor CD8+ T Cells - Li, Jing; He, Yi; Hao, Jing; Ni, Ling; Dong, Chen (Frontiers in Immunology, 2018)
Eomes, a T-box transcription factor, is known important for both function and homeostasis of effector and memory T cells, but was recently also implicated in CD8+ T cell exhaustion. However, whether and how Eomes might regulate effector functions or exhaustion of CD8+ T cells, especially in the tumor setting, is unknown. Here we first show, as tumor progressed, Eomes expression was elevated in tumor-infiltrating CD8+ T cells, especially in PD-1+Tim-3+ exhausted CD8+ T cells. Complete loss of Eomes in T cells resulted in impaired development of anti-tumor CTLs, whereas deletion of one allele of Eomes in T cells decreased development of exhausted CD8+ T cells, which offered better tumor control. Integrative analysis of RNAseq and ChIPseq of Eomes-overexpressing T cells revealed that high levels of Eomes expression directly controlled expression of T cell exhaustion genes, such as Havcr2. In addition, Eomes might compete with T-bet binding to regulatory genomic loci to antagonize T-bet functions. Collectively, Eomes exerts bimodal functions in CD8+ T cells in tumor.